Apexification in Non-Vital Teeth with Immature Roots: Report of Two Cases - Vieira Silva, Rogério; Ferreira Silveira, Frank; Nunes, Eduardo (Iranian Endodontic Journal, 2014)
Apexification is a method of inducing apical closure for non-vital immature permanent teeth. During this treatment a mineralized barrier is induced [with long term calcium hydroxide (CH) treatment]; or artificially created [with mineral trioxide aggregate (MTA) plug]. This article describes two cases of apexification in immature necrotic teeth treated with these two different techniques. After 6 years of follow-up, clinical and radiographic control showed that both treatments were successful.